2021
DOI: 10.18203/2349-3933.ijam20210265
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution computed tomography as a non-invasive imaging biomarker for interstitial lung diseases: a tertiary center study

Abstract: Background: Interstitial lung diseases (ILD) are a heterogeneous group of non-neoplastic disorders resulting from damage to the lung parenchyma by varying patterns of inflammation and fibrosis. With high-resolution computed tomography (HRCT) the pattern of lung damage can be mapped accurately which may help to identify specific ILD.Methods: 65 diagnosed cases of ILD by HRCT who were admitted to a tertiary care chest hospital, formed the study group. All these patients also underwent histopathological confirmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This finding is in correlation with the well-known fact that ILD affects men more commonly. 11 CXR made a positive diagnosis of ILD in66.7% while HRCT was positive in 91.70% of our study subjects. A study conducted in Pakistan also reported that CXR was positive for ILD in 58.39% of their study participants.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…This finding is in correlation with the well-known fact that ILD affects men more commonly. 11 CXR made a positive diagnosis of ILD in66.7% while HRCT was positive in 91.70% of our study subjects. A study conducted in Pakistan also reported that CXR was positive for ILD in 58.39% of their study participants.…”
Section: Resultsmentioning
confidence: 57%
“…20 Senger et al assessed the HRCT of 60 patients in India for the different interstitial lung diseases and compared the results with histopathology reports and reported a good correlation between the HRCT diagnosis of the different subtype of ILD and it histopathology diagnosis. 11 We stratified the diagnostic accuracy of CXR as compared to the HRCT for age and gender. We found no significant difference in the ability of CXR to diagnose ILD in either sex or at older age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation